Bali Art Festival and the Futures of Regenerative Tourism: Rethinking Festival Practices in Sustaining Intangible Cultural Heritage - Agung Parameswara (Centre of Excellence in Tourism Udayana University, 2026)
The role of festivals in challenging the perception of local identity and regenerating intangible cultural heritage can be very important and, in the case of the oldest festival in Indonesia, Bali Art festival, is the most important outcome for sustaining intangible cultural heritage and regenerative tourism model. Drawing upon focus group discussions with artists, scholars, and festival stakeholders, the paper explores how PKB, held annually since 1979, navigates the complexities of artistic preservation, community participation, cultural policy, and tourism development. While originally initiated to support cultural continuity amid growing tourism, PKB has evolved into a site of intergenerational artistic transmission and creative renewal. The paper situates PKB within broader discourses on regenerative tourism, emphasizing its alignment with Balinese cosmology, particularly the practice of ngayah—voluntary service rooted in spiritual and communal devotion. The findings highlight PKB’s successes in promoting place-based identity, youth involvement, and policy-driven continuity, but also reveal structural challenges, including bureaucratic fragmentation, spatial inequity, under-compensation of artists, and the risk of cultural homogenization. By analyzing PKB as a “living lab” of regenerative tourism, the research contributes to current debates on how cultural festivals can evolve beyond commodification and serve as agents of cultural resilience, social learning, and community empowerment. The Bali art festival offers an important case study for understanding the transformative potential of festivals in safeguarding intangible cultural heritage and fostering tourism practices that are culturally embedded, socially just, and ecologically restorative.